May Measurement Month 2018: an analysis of blood pressure screening results from Ecuador. (28th August 2020) - Peñaherrera, Ernesto; Beaney, Thomas; Ster, Anca Chis; Poulter, Neil R; Villalba, Jose; Ramirez, Maria Isabel; Duarte, Yan; Caceres, Silvia; Mora, Cecilia; Peñaherrera, Ruben; Avila, Elisa; Arteaga, Fabricio; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative by the International Society of Hypertension (ISH) aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programmes worldwide. An opportunistic cross-sectional survey of volunteers aged ≥18 was carried out in May 2018. A volunteer cross-sectional survey was carried out in May 2017 across 33 health centres. Blood pressure measurement, the definition of hypertension (HTN) (mean of the 2nd and 3rd BP measurement ≥ 140/90 mmHg or who were medicated for high BP), and statistical analysis followed the standard MMM protocol. In total, 11 922 individuals (53.7% female) were screened during MMM18. After multiple imputation, 4563 (38.3%) had HTN. Of individuals not receiving antihypertensive medication, 1302 (15.0%) were hypertensive. Of individuals receiving antihypertensive medication, 933 (28.6%) had uncontrolled BP. MMM18 was the largest BP screening campaign done in Ecuador. Hypertension was detected in 38.4% of those screened and almost 4 out of 10 were either not on treatment or were not controlled to the BP goal. These results suggest that appropriate screening can help to identify a significant number of people with high BP. These data should attract the attention of doctors and health care system in Ecuador.